2018
DOI: 10.1007/s10803-018-3695-6
|View full text |Cite
|
Sign up to set email alerts
|

Autism Traits, Sensory Over-Responsivity, Anxiety, and Stress: A Test of Explanatory Models

Abstract: The relationship between autistic traits, stress, and anxiety experienced by the general population was investigated using an adult sample that evaluated the suitability of three theoretical models proposed by Green and Ben-Sasson. Participants completed online questionnaires that were analysed using structural equation modelling and partial correlation analyses. Of the models tested, the model that proposed SOR and stress as mediators of the relationship between autistic traits and anxiety was able to explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 62 publications
1
23
1
Order By: Relevance
“…This too supports the primary SOR model proposed by Green and Ben-Sasson (2010) indicating that SOR may be an underlying cause of child anxiety (Lane et al, 2012). A recent paper by Amos et al (2019), also examined this relationship in a group of children with ASD. These investigators substantiated the primary SOR model, indicating that SOR and stress were mediators between autistic traits in the general population and anxiety.…”
Section: Adhd Cortisol Electrodermal Response and Anxiety: Findingmentioning
confidence: 99%
See 2 more Smart Citations
“…This too supports the primary SOR model proposed by Green and Ben-Sasson (2010) indicating that SOR may be an underlying cause of child anxiety (Lane et al, 2012). A recent paper by Amos et al (2019), also examined this relationship in a group of children with ASD. These investigators substantiated the primary SOR model, indicating that SOR and stress were mediators between autistic traits in the general population and anxiety.…”
Section: Adhd Cortisol Electrodermal Response and Anxiety: Findingmentioning
confidence: 99%
“…Our previous work established a link between SOR and anxiety (Reynolds and Lane, 2009; Lane et al, 2012) in children with ADHD, and this link has been well substantiated in other diagnostic groups of children and adults, particularly those with ASD (Bart et al, 2017; Carpenter et al, 2018; Syu and Lin, 2018). Within the ASD literature, testable models have been proposed that link SOR, anxiety, and autistic traits as well as aspects of physiological and behavioral stress (Green and Ben-Sasson, 2010; Amos et al, 2019). As noted earlier, Amos et al (2019), found that SOR and stress mediated the relationship between autistic traits and anxiety, in that the relationship between autistic traits and anxiety became non-significant after accounting for the effects of SOR and stress.…”
Section: Research Developments In Adhd With Links To Sensory Responsimentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, higher anxiety symptoms were significantly associated with more dismissing and dysfunction. One possible explanation is that anxiety is highly characterized by sensory overresponsivity (Amos et al, 2019), which refers to the subjective experience of sensory overload, such as noise or light. This feature suggests a possibility for higher-anxiety parents to show overresponse to children's anger expressions, thus resulting in denying the children's display of anger (dismissing) or becoming impulsive and reckless about the emotional situations (dysfunction).…”
Section: Role Of Psychopathology On Esmentioning
confidence: 99%
“…In particular, sensory hyperreactivity can greatly impact quality of life and has been found to correlate with clinically elevated levels of anxiety in both autistic children and adults (Carpenter et al, 2018;Green et al, 2012;Green & Ben-Sasson, 2010;Hwang et al, 2019;MacLennan et al, 2020). It is therefore unsurprising that aversive sensory environments have been suggested to be a barrier for autistic adults engaging in spaces, both public and occupational (Amos et al, 2019). Therefore, understanding the complexities of sensory experiences has important implications for autistic people's physical and mental wellness, social inclusion, and future prospects.…”
Section: Introductionmentioning
confidence: 99%